ANALISIS ANGGARAN TENAGA KERJA SEBAGAI ALAT PERENCANAAN DAN PENGENDALIAN BIAYA LABOR BUDGET ANALYSIS AS A COST PLANNING AND CONTROL TOOL - Ananda Febriyani Tarigan; Sheila Afriliani (INTERNATIONAL, Journal of Sharia Business Management, 2025)
This study aims to analyze the labor budget as a tool for planning and controlling costs within a company. The labor budget plays an important role in allocating human resources and controlling operational costs in order to achieve organizational objectives. This research employs a descriptive qualitative method using primary and secondary data sources. Primary data were obtained through interviews with relevant parties, while secondary data were collected from company documents related to labor budgeting and labor cost realization. Data collection techniques included interviews, observation, and documentation. The results indicate that the labor budget has been used as a guideline for planning labor requirements and allocating costs such as salaries, allowances, and overtime. However, discrepancies between budgeted and actual labor costs were identified, mainly due to increased overtime expenses and adjustments in allowances. Nevertheless, the labor budget still functions effectively as a cost control tool by enabling management to identify deviations and conduct evaluations for improvement in subsequent periods.